SCIENCE FOR PRODUCTION: REGIONAL SCIENTIFIC-PRACTICAL SEMINAR "MODERN METHODS OF CREATING AND DEVELOPING OF HIGHLY PRODUCTIVE FOREST PLANTATIONS" - Vysotska, N. Yu. (Forestry and Forest Melioration, 2018)
The regional scientific and practical seminar “Modern methods of building and developing highly productive forest plantations” took place in Kharkov on the 22–23th of September, 2016. State Forest Resources Agency of Ukraine, Society of Foresters of Ukraine, Kharkov Regional Society of Foresters of Ukraine, Kharkov Regional Administration of Forestry and Hunting, and Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotskiy (URIFFM) were the organizers of the event. The seminar was devoted to the main issues on introduction of the newest technologies of artificial forest regeneration and afforestation to ensure the efficiency of growing quality forest crops, as well as forestry activities aimed at natural seed renewal of stands, in particular of complex felling.